Care Assistant for Older Persons - Sasat, Siriphan; Pakdeeporm, Tuanjai (Journal of Health Science of Thailand, 2017)
There has been has been an increasing need for care assistant in the Thai society due to the declining of family ability to care for their ill health or dependent elderly relatives. The documentary research was carried out aiming at reviewing literature and concept synthesis on care assistant, and recommendations on policy and practice. Care assistants were non professional carers who received formal training, for example, in Canada, they had to undergo training for certification or prior learning assessment leading to recognition for registration. Their work places were patient’s home and long-term care institutions under supervision of registered nurses, psychiatric nurses or licensed practical nurses. In the United States, they had to undertake at least 75 hours of formal training or 6-8 weeks of nursing assistant program, online distance education and had to pass the examination in order to be qualified to work at hospitals, clinics, patient’s homes, or other health care institutions. In United Kingdom, health care assistant had to undertake on-the-job training, open learning, e-learning, or formal training from college, ranging from 2-week to 2-month courses. There were on the job observation and question for obtaining the National Vocational Qualification and registration in order to work at primary care unit, hospital, residential home, or at home under health professionals supervision. In Thailand, there were a number of care assistant’s curriculums with different evaluation criteria while no quality assurance system had been applied. The permission to open training school can be obtained from the Ministry of Education and there was an initiative for curriculum development at the vocational level. The problems were care assistant received no recognition from professional organisation and some of their caring procedures had invaded nursing profession which may violate the Nursing Act. These findings suggest that there were needs to develop a clearer care assistant’s competency and indicate a proper body for curriculum development and granting permission in order to response to the need of the society. Applying quality assurance, set-up a welfare system, and promotes continuing study and learning opportunity for care assistant were also needed. Further studies should focus on quality assurance, curriculum improvement, care assistant classification, and registration system.